Bioactive substrates for human retinal pigment epithelial cell growth from elastin‐like recombinamers. Issue 3 (14th May 2013) - Singh, Amar K.; Srivastava, Girish K.; Martín, Laura; Alonso, Matilde; Pastor, J. Carlos
Abstract The aim of this study was to investigate the use of bioactive RGD‐containing elastin‐like recombinamers (ELR‐RGDs) as a substrate that can maintain human retinal pigment epithelial cell (hRPE) phenotype and growth pattern. Results obtained are compared with previously published behavior of ARPE19 cells. The extension of these results to hRPE is required because ARPE19 cells cannot be used clinically to treat age‐related macular degeneration. hRPE cells were isolated, cultured, seeded, and grown on surface of glass, treated polystyrene (TCP), and solvent‐cast ELR‐RGD and ELR‐IK film with no specific sequence. Cells were analyzed to study cell adhesion, proliferation, morphology, and RPE65 protein expression by staining with diamidino‐2‐phenylindole, Rhodamine‐Phalloidin, and anti‐RPE65 antibody at 12, 24, 72, 120, 168, and 360 h. hRPE cells always grew better on ELR‐RGD than on glass and ELR‐IK but not on TCP. The kinetic hRPE growth curves confirmed that growth differences started to appear at 24 h for these surfaces in ascending order of cell growths, namely glass, ELR‐IK, ELR‐RGD, and TCP. There was a clear difference at 360 h. ELR‐RGD maintained hRPE cells stable morphology and RPE65 protein expression. ELR‐RGD seems to be a good substrate for growing hRPE cells with stable morphology and RPE65 protein expression. As such, this work confirms our hypothesis regarding ELR‐RGD substrates viability, which can be used as a Bruch's membrane prosthesis for further studies in animals. However, these results must subsequently be extrapolated to use of hRPE cells in animals to evaluate them as a transplantation vehicle in human. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 639–646, 2014.